PERCEIVED ORGANIZATIONAL SUPPORT DAN ORGANIZATIONAL CLIMATE DALAM MEMBENTUK OCCUPATIONAL COMMITMENT - Danan Satriyo Wibowo (Program Studi S1 Psikologi, 2022)
Work is a form of self-actualization effort, where work requires support and a supportive environment so that the performance can be carried out productively and has a commitment to work, this condition cannot be separated from the existence of organizational support (perceived organizational support) and organizational climate ( organizational climate) which provides perceptions for employees at work and involvement in the work they do (occupational commitment. The purpose of this study is to reveal and explain how perceived organizational support (POS) and organizational climate in forming occupational commitment in the education profession (teachers and lecturers) and medical personnel (nurses). The method used is quantitative with a cross sectional survey design model, with a sample of educators (teachers and lecturers) and health workers (nurses). The results show that perceived organizational support affects on in forming occupational commitment. While the results of organizational climate research have no effect in forming occupational commitment. Perceived organizational support and organizational climate together have an influence in forming occupational commitment.